2008
DOI: 10.1086/587957
|View full text |Cite
|
Sign up to set email alerts
|

Heating the Solar Wind by a Magnetohydrodynamic Turbulent Energy Cascade

Abstract: Astrophysical Journal, 677, pp. L71-L74, http://dx.doi.org./10.1086/587957International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
157
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(167 citation statements)
references
References 21 publications
6
157
4
Order By: Relevance
“…The estimation of the turbulent energy transfer rate has also shown that the electromagnetic turbulence may explain the observed solar wind non-adiabatic profile of the total proton temperature (Vasquez et al 2007;Marino et al 2008;MacBride et al 2008;). However, this explanation does not take into account a possible ion temperature anisotropy, known to be important in the solar wind (see Sect.…”
Section: Energy Transfer Ratementioning
confidence: 98%
See 1 more Smart Citation
“…The estimation of the turbulent energy transfer rate has also shown that the electromagnetic turbulence may explain the observed solar wind non-adiabatic profile of the total proton temperature (Vasquez et al 2007;Marino et al 2008;MacBride et al 2008;). However, this explanation does not take into account a possible ion temperature anisotropy, known to be important in the solar wind (see Sect.…”
Section: Energy Transfer Ratementioning
confidence: 98%
“…Solar wind energy transfer rates have been shown to lie between ∼ 0.1 kJ kg −1 s −1 (in Ulysses high latitude fast wind data, far from the Earth) and up to ∼ 10 kJ kg −1 s −1 in slow ecliptic wind at 1 AU Marino et al 2008Marino et al , 2012MacBride et al 2008;). The rate of occurrence of the linear scaling in the solar wind time series, and the corresponding energy transfer rate, have been related to several solar wind parameters.…”
Section: Energy Transfer Ratementioning
confidence: 99%
“…Using the previously published analyses of Helios data, together with Advanced Composition Explorer (ACE) data, Vasquez et al [61] obtained an expression describing proton heating at 1 AU that varies with wind speed and observed temperature. More recently, these results have been extended to include high latitudes [103,104] and non-zero cross helicity (called 'imbalanced turbulence' by some) [62].…”
Section: Heatingmentioning
confidence: 99%
“…When the process results in a power law spectrum at small wavenumbers, with constant negative flux of some quantity that is conserved in the ideal limit, the system is said to sustain an inverse cascade of that quantity. It is a well known feature of nonlinear dynamics that has been reviewed extensively [27][28][29], in particular in the context of two dimensional (2D) Navier-Stokes fluids [30], and that has also been observed in astrophysical plasmas [31][32][33].…”
Section: Introductionmentioning
confidence: 99%